2022
DOI: 10.3389/fcell.2022.1010818
|View full text |Cite
|
Sign up to set email alerts
|

From regeneration to osteoarthritis in the knee joint: The role shift of cartilage-derived progenitor cells

Abstract: A mount of growing evidence has proven that cartilage-derived progenitor cells (CPCs) harbor strong proliferation, migration, andmultiple differentiation potentials over the past 2 decades. CPCs in the stage of immature tissue play an important role in cartilage development process and injured cartilage repair in the young and active people. However, during maturation and aging, cartilage defects cannot be completely repaired by CPCs in vivo. Recently, tissue engineering has revealed that repaired cartilage de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 121 publications
0
3
0
Order By: Relevance
“…It is essential to explore the dose response and time-dependence of TMF on chondrocyte hypertrophy in OA cartilage, and these were not determined in the present study. In vitro study, two concentrations of TMF were studied to inhibit the expression of ColX and Runx-2, which are the biomarkers of OA chondrocyte hypertrophy (64). However, the absence of more concentrations to validate the concentration-dependent TMF inhibition of OA chondrocyte hypertrophy was also a limitation of the present study.…”
Section: Discussionmentioning
confidence: 95%
“…It is essential to explore the dose response and time-dependence of TMF on chondrocyte hypertrophy in OA cartilage, and these were not determined in the present study. In vitro study, two concentrations of TMF were studied to inhibit the expression of ColX and Runx-2, which are the biomarkers of OA chondrocyte hypertrophy (64). However, the absence of more concentrations to validate the concentration-dependent TMF inhibition of OA chondrocyte hypertrophy was also a limitation of the present study.…”
Section: Discussionmentioning
confidence: 95%
“…As previous studies have revealed, initially, CPCs situated in the superficial layer become activated and proliferate to fill the area with FCs. 74 75 However, only a small fraction of FCs have the ability to differentiate into SCs and migrate towards the deeper layers of cartilage tissue. 76 As the SCs mature, they undergo a transformation into HCs that are typically found at the tidemark of the cartilage tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The regenerative potential of chondroprogenitor cells in adult AC tissues is a topic of debate. Prg4-producing cells inhabit both the SFZ of cartilage and the synovial membrane [ 20 , 75 , 76 ]. Using the osteochondral defect model, Decker and collaborators [ 68 ] showed that the injury site was filled by the progeny of Prg4-positive cells within 7 days after surgery.…”
Section: Regenerative Potential Of Adult Superficial Progenitors Of A...mentioning
confidence: 99%